ELASTISITAS PENYERAPAN TENAGA KERJA SEKTORAL TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT UPAH DI PROVINSI JAWA TIMUR PADA TAHUN 2012-2017 - Juniardi Putra Hariyanto; Petrus Edi Suswandi Edi Suswandi; Fajar Wahyu Prianto (Relawan Jurnal Indonesia, 2018)
This study aims to determine the level of elasticity of sectoral employment absorption labor in East Java Province. The data used is secondary data obtained from the office of National Statistics Institutionand other related institution. This type of research is correlational and regression which aims to find out whether there is a relationship between variables where the variables used in this study are Economic Growth (GDP), and Wage Rateon Labor Absorption in East Java Province. The method used in this study is panel data with the Common Effect approach and is associated with descriptive analysis. Based on the results of the study show that the level of elasticity of sectoral employment in East Java Province is mostly in the inelastic positive and inelastic negative category, meaning that every increase in value of 1 in economic growth and wage ratewill cause an increase in the velueof laborabsorbed by less than 1 (inelastic positive), on the contrary if there is an increase in value of 1 in economic growth and wage ratewill cause a decrease in the number of laborabsorbed by less than 1 (negative inelastic). only in the agricultural sector is positive elastic, meaning that every increase in value of 1 in economic growth and wage rate will cause an increase in the number of laborabsorbed by more than 1.